(untitled) (Zaporizhzhia Historical Review, 2021)
The article is devoted to the symbols of Zaporizhzhyan Cossackhood. The place of cross-anchor in the heraldry of Cossack starshyna of those times and its usage in XIV-XVIIIth centuries is being explored.